The levels of primary school children in their attitude towards labour - Jakimova, I. (Psichologija, 1988)
In the present paper the instrumental theory of vocational interests is used as a theoretical basis. Models and a diagnostic technique of primary schoolchildren’s attitude towards labour are presented, the results of preliminary research are provided.